Strategies To Maintain Customer Loyalty In Indonesia's Pandemic - Woro Utari; Made Yudi Darmita (JURNAL EKBIS, 2022)
The purpose of this study is to formulate a strategy carried out by cafe owners so that their customers remain loyal, especially during the Pandemic. The subjects of this research are 10 cafes in Surabaya . The informants in this study were cafe visitors aged over 17 years and cafe owners/managers. The analysis technique used descriptive statistical analysis and qualitative analysis . The results show that cafe customers in Surabaya are generally loyal, customer loyalty is reflected in recommending to others and doing word of mouth. Efforts that must be made by cafe owners are how to maintain customer loyalty. Strategies that can be done to maintain customer loyalty through several dimensions are providing satisfaction to customers, building customer trust, building emotional bonds andproviding good experiences to customers .